Impact of Audit Tenure, Fee and Auditor Specialist on Audit Quality: Study of Indonesian Manufacturing Firms - M Huda Marizqi; Fitra Dharma (Pustaka Peradaban, 2023)
ABSTRACTProblems related to low audit quality are significant problems and require careful consideration, because they can hinder the preparation of accurate audit reports. This concern is not only limited to Public Accounting Firms but also extends to Public Accounting Firms that have high credibility, such as the Big Four. Several examples of low audit quality within the Big Four were highlighted in recent announcements by the PCAOB (Public Company Accounting Oversight Board) in 2016 and 2017, which resulted in sanctions against several of these companies. This situation requires research to assess the impact of auditor specialization, audit tenure and audit fees on audit quality in manufacturing companies audited by the Big Four Public Accounting Firms. This research used purposive sampling to obtain a total sample of 172 companies. The data analysis technique used in this research is multiple regression analysis using SPSS 23. The research results show that audit tenure, audit fees and auditor specialization influence audit quality.